(untitled) (World Bulletin of Public Health, 2024)
Bronchial asthma occupies a rather high place among noncommunicable diseases of children and adolescents. Thus, the statistical register for recent years has revealed that among children of Uzbekistan under 14 years of age, the prevalence of bronchial asthma is 18.3 and 64.2 (per 100000 children), and among adolescents 23.3 and 92.8 (per 100000 adolescents) respectively, with a tendency to increase by 10-30%.